Systematic Literature Review: Efektivitas Ekstrak Kopi sebagai Antioksidan dalam Mengatasi Photoaging - Ratri, Oktavia Lestyaning; Ebtavanny, Tamara Gusti; Puspita, Oktavia Eka (Brawijaya University, 2021)
Aging of the skin due to exposure of UV rays is referred as photoaging. Photoaging causes dry skin, wrinkles, darker skin pigmentation, and reduced skin firmness. The effect of photoaging can be treated by compounds that have antioxidant activity. Coffee contains polyphenols (caffeic acid and chlorogenic acid) which can inhibit the formation of ROS free radicals. This makes coffee an antioxidant potential in photoaging treatment. This study aims to determine the effectiveness of coffee extract as an antioxidant in photoaging treatment. The method used in this study is Systematic Literature Review. A comprehensive literature search was conducted using the Harzing's Publish or Perish application on several databases, such as Google Scholar, PubMed, Scopus, and Crossref using the keywords